ANALISIS KELESTARIAN PENGELOLAAN HUTAN RAKYAT DI KAWASAN BERFUNGSI LINDUNG - Alan Purbawiyatna; Hariadi Kartodihardjo; Hadi S. Alikodra; Lilik Budi Prasetyo (Graduate School Bogor Agricultural University (SPs IPB), 2011)
Private forest at Kuningan district, West Java province, has shown increasing coverage at average of 5,86% during 2003-2009. The forest has served as protection area beside state protection forest in Kuningan district. The forestland status is private property whereas forthe owner has served as production forest. The aim of this research was to assess performance of that private forest management, using set of criteria and indicators for sustainable community-based forest management developed by the Indonesian Ecolabelling Institute/LEI (2002). The result shows that management practiced fail to fulfill the standard. Nevertheless private property rights of the forest land enabled the owner to invest in forest development for economic benefit, which public perceived having a positive impact in the form of environmental services. Lack of technical and institutional capacity in forest management need to be improved to enable the owner gain economic benefit while provide environmental services for public. Key words: private forest, sustainable forest management, protection area, institution